Population dynamics of major fish species and socioeconomic status of inland water fisheries in the Kebbi State, Nigeria - Bawa, Dalhatu Yahaya (2019)
Kebbi State is blessed with abundant fisheries resources in their riverine system that contributes to the artisanal fishermen's life in Kebbi State. However, basic information such as fish species composition, age structure, growth, mortality, habitat status and socioeconomic profile of fishermen for fisheries management are not available in the Kebbi State so far. A study was conducted on fish species composition, catch-per- unit-effort (CPUE), population dynamics of three (3) selected major species and socioeconomic status of small-scale fisheries from the Kebbi State, Nigeria between January and December 2017. Fish sample were collected from three (3) selected fishing communities namely Argungu, Sabiyel and Yauri. Water quality parameters were recorded in situ using YSI 556 MDS (YSI Incorporated, USA) professional handled multi-parameter recorder, these include dissolved oxygen, pH, temperature, ammonia, phosphate and total dissolved solid, meanwhile chlorophyll-a were determined ex-situ. The age, growth, mortality and recruitment of major fish species (Bagrus bayad, Hyperopsis bebe occidentalis and Synodontis nigrita) were investigated based on monthly length-frequency data, using FISAT software. A set of structured questionnaire was used to collect all information from the fishermen and total of 289 fishermen were approached and the data collected was analyzed using SPSS software (version 22.0). In total 18 fish species belonging to 11 families were identified from the waters of Kebbi State. Among the 11 families Mormyridae was the highest with (16.66%) comprising of three species. The average monthly CPUE was 37.44 kg/ gill net/hour and the highest catch was recorded during July to September. The CPUE of fishes varied significantly (p < 0.05) among the different stations. A total of 11 different types of gears fishing gears was recorded, these include: gill net, surrounding net, cast net, beach seine net, trap net, gura trap, Indrutu, hook and line, Ara trap and Kawari. The study of population dynamics parameters revealed that Bagrus bayad, Hyperopsis bebe occidentalis and Synodontis nigrita attained an average growth rate/year of 4.56cm, 3.73cm and 3.71cm respectively with a recruitment pattern of two major recruitment events per year. The natural mortality rate (M) of B. bayad, H. occidentalis and S. nigrita were 0.97 yr⁻¹, 0.91 yr⁻¹ and 0.90 yr⁻¹ while fishing mortality rate (F) was 0.56 yr⁻¹, 0.75 yr⁻¹ and 0.99 yr⁻¹ respectively. Results from the analysis of the exploitation rate (E) shows that B. bayad (0.37 yr⁻¹) and H. occidentalis (0.45 yr⁻¹) were 26% and 10% under fished while S. nigrita (0.52 yr⁻¹) was slightly above optimum level of exploitation (E = 0.50). This implies that the fish stocks in the study area are underexploited as a subsistence fishery. The socio- demographic study revealed that most of the fishermen were between 31 and 40 years old (31.8%). All the fishermen are Muslim (100%); with 97.9% fishermen were engaged in fishing as their occupation. However, only 41.9% had the formal education in Islamic field of studies. Meanwhile, about 49.5% were categorized in the low income earners of the fisher’s community. This result implies that the fish stocks in the study area are underexploited. Fishermen community largely depends on fishing as their source of livelihood and daily income was USD 1.50 which is sufficient to survive sustainably. This finding confirms the close relationship between fishery resource exploitation rates and the socioeconomic development of fishermen at the individual level and as an alternative source of available resources at the community and State level in general. There is a need to diversify into aquaculture to reduce the impact on wild fish population.